Effect of Agonist-Antagonist Paired Set and Traditional Set Strengthening Exercise Methodson Single-Leg Hop Performance - Gadiza Raiznintha Permatasari; RA Meisy Andriana; I Putu Alit Pawana (Surabaya Physical Medicine and Rehabilitation Journal, 2021)
Background: Functional activities mostly done in daily life such as jumping, walking, running, and stairs ascending-descending require dynamic stability of the knee. The knee joint dynamic stability is required to have effective and efficient functional activities and to avoid injury when performing them. It can be achieved by increasing muscle strength through strengthening exercises with the aim of balancing the agonist muscles (quadriceps femoris) and antagonist muscles (hamstring) using the agonist- antagonist paired set (APS) method.Aim: The aim of this study is to find out the effect of strengthening exercise using APS method, compared to traditional set (TS) method, on single-leg hop performance.Material and Methods: The subjects of this study were 14 untrained healthy men aged 18-40 years old divided into 2 intervention groups, APS group and TS group. The variable evaluated was the distance of single-leg hop (SLH).Results: The results of this study showed a significant increase in SLH distance in APS group (p=0.005) and TS group (p<0.001) with no significant difference between the two groups (p = 0.933).Conclusion: Quadriceps femoris and hamstring muscle strengthening exercises in both APS and TS methods increase SLH distance although there is no difference between them. The APS method has an advantage compared to the TS method in terms of a relatively shorter time with comparable results.